RNA editing landscape of adipose tissue in polycystic ovary syndrome provides insight into the obesity-related immune responses - Chen, Hanxiao; Li, Tongtong; Gao, Rui; Cheng, Meng; Zhang, Qiong; Liu, Xiumei; Chen, Mingli; Liao, Xin; Qin, Lang (Frontiers in Endocrinology, 2024)
Background: Polycystic ovary syndrome (PCOS) is the most common reproductive-endocrine disorder with wide-ranging metabolic implications, including obesity. RNA editing, a posttranscriptional modification, can fine-tune protein function and introduce heterogeneity. However, the role of RNA editing and its impact on adipose tissue function in PCOS remains poorly understood. Methods: This study aimed to comprehensively analyze RNA editing events in abdominal and subcutaneous adipose tissue of PCOS patients and healthy controls using high-throughput wholegenome sequencing (WGS) and RNA sequencing.Results: Our results revealed that PCOS patients exhibited more RNA editing sites, with adenosineto-inosine (A-to-I) editing being prevalent. The expression of ADAR genes, responsible for A-to-I editing, was also higher in PCOS. Aberrant RNA editing sites in PCOS adipose tissue was enriched in immune responses and interleukin-12 biosynthetic process, tumor necrosis factor (TNF) signaling, nuclear factor kappa B (NF-κB) signaling, Notch signaling, terminal uridylyl transferase 4 (TUT4), hook microtubule tethering protein 3 (HOOK3), forkhead box O1 (FOXO1) were identified to be of significant differences. Differentially expressed genes (DEGs) in PCOS adipose tissue were enriched in immune responses compared with controls, and the DEGs between subcutaneous and abdominal adipose tissue also enriched in immune responses, suggesting the important role of subcutaneous adipose tissue. Furthermore, we identified the correlations between RNA editing levels and RNA expression levels of specific genes, such as ataxia-telangiectasia mutated (ATM) and mucosaassociated lymphoid tissue lymphoma translocation protein 1 (MALT1) in inflammation pathways and ATM, TUT4, and YTH N6-methyladenosine RNA binding protein C2 (YTHDC2) in oocyte development pathway.Conclusions: These findings suggest that RNA editing dysregulation in PCOS adipose tissue may contribute to inflammatory dysregulations. Understanding the interplay between RNA editing and adipose tissue function may unveil potential therapeutic targets for PCOS management. However, further research and validation are required to fully elucidate the molecular mechanisms underlying these associations.